PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM ERA DIGITAL - Topani, Iip Nurul (Universitas Khairun, 2024)
The development of e-commerce in Indonesia has made transactions easier for consumers. However, the increasing number of cases of fraud and violations of consumer rights in online transactions is a serious concern. This research aims to analyze legal protection for consumers in ecommerce transactions in Indonesia, with a focus on the role of the Consumer Protection Law and the Information and Electronic Transactions Law. This research will also examine the effectiveness of consumer protection institutions in handling consumer disputes in the digital era and provide policy recommendations to improve consumer protection in electronic transactions.